Designing Interactive Multimedia-Based Learning Media Using Augmented Reality in Basic Computer and Networking Subjects Computer and Basic Networking for School Expertise Package Vocational High School - Yandi, Zidan Fitri; Munir, M; Rasim, R (Universitas Pendidikan Indonesia, 2021)
Learning infrastructure is one of the supporting factors for vocational high school learning activities for the Computer and Informatics Engineering expertise program. Less effective learning media used by teachers as well as understanding and activeness of students in the learning process of this research background. The main objective of this research is to design and implement interactive multimedia based on Augmented reality with Auditory, Intellectually, and Repetition (AIR) learning models to determine the cognitive enhancement of students in learning network topology on basic computer and network subjects. Augmented reality-based interactive multimedia uses a comprehensive life cycle development model (SHM) and the research method used is quantitative with a sample of class X (ten) Multimedia students of SMK Negeri 1 Cipatat. From this research, the results obtained: (1) interactive multimedia is good and suitable for use. Obtained media value of 82% and material of 90.74% which is very well interpreted by media experts and subject teachers. (2) Interactive multimedia can improve students' cognitive with the acquisition of an average value of 0.697 with criteria that have